Modified Technique of Setting Capsulotomy Thickness in Reducing Capsulotomy-Related Complications During Femtosecond Laser-Assisted Cataract Surgery: A Prospective, Comparative Cohort Study - Takeshi Teshigawara; Miki Akaishi; Yuki Mizuki; Masaki Takeuchi; Seiichiro Hata; Akira Meguro; Nobuhisa Mizuki (Ophthalmology and Therapy, 2023)
Abstract Introduction Although uncommon, incomplete capsulotomy, anterior capsule tags and anterior capsule tears are still encountered during femtosecond laser-assisted cataract surgery (FLACS), resulting in surgical complications. This highlights the need to improve femtosecond laser-assisted capsulotomy technique to reduce capsulotomy-related complications. Therefore, the purpose of this study was to investigate the efficacy of a newly developed, modified technique of setting capsulotomy irradiation thickness in lowering the incidence of capsulotomy-related complications in FLACS. Methods This open-label prospective, comparative cohort study included 440 eyes (220 patients) treated with FLACS using the LenSx laser system (Alcon Laboratories, Inc. Fort Worth, TX, USA). Varying capsulotomy irradiation thicknesses were applied in each eye of the same patient. In Group 1, capsulotomy irradiation thickness was set between the upper edge of the highest point of the anterior capsule and the lower edge of the lowest point of the anterior capsule (modified technique). In Group 2, this was set between the center of the highest point of the anterior capsule and the center of the lowest part of the anterior capsule (conventional technique). Incidence rates of incomplete capsulotomy, anterior capsule tags and tears, and posterior capsule tears were compared. Results Preoperative baseline characteristics showed no significant differences. Mean total of the irradiation thicknesses was 877.1 ± 81.9 µm in Group 1 and 808.9 ± 80.0 in Group 2, with a statistically significant difference (P < 0.001). Incidences of incomplete capsulotomy were 1.8% and 7.7%, anterior capsule tags were 2.3% and 8.6%, and anterior capsule tears were 0% and 3.2% in Groups 1 and 2, respectively. These differences were statistically significant (P = 0.006, 0.005, and 0.015, respectively). No posterior capsule tears were reported in either group. Conclusion The modified technique for capsulotomy in FLACS may significantly reduce the occurrence of capsulotomy-related complications, maximizing the benefits of FLACS.